1992
DOI: 10.1093/schbul/18.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and Functioning in First-Episode Schizophrenia

Abstract: One current view of schizophrenia is that its clinical and functional features show a deteriorating course, particularly for negative symptoms. However, this is difficult to study in chronic patients who have been exposed to pharmacologic treatment and institutionalization. Examining first-episode (FE) patients can help clarify which symptoms are present initially and how the symptom pattern is linked to functioning. We evaluated a sample of 37 FE patients with schizophrenia and compared them to 70 other schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 41 publications
8
52
1
2
Order By: Relevance
“…No sex differences were found for either neuropsychological or clinical change in this sample, although sex differences in the severity and course of schizophrenia have been documented (Shtasel et al, 1992a). This negative finding may reflect sample size.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…No sex differences were found for either neuropsychological or clinical change in this sample, although sex differences in the severity and course of schizophrenia have been documented (Shtasel et al, 1992a). This negative finding may reflect sample size.…”
Section: Discussioncontrasting
confidence: 54%
“…Cross-sectional studies suggest that negative symptoms correlate more with neuropsychological change than do positive symptoms (Bilder et al, 1985;Andreasen et al, 1990;Shtasel et al, 1992a). Longitudinally, Saykin et al (submitted for publication) found correlations between improvement in negative symptoms and neuropsychological change.…”
Section: Introductionmentioning
confidence: 99%
“…After informed consent was obtained, participants underwent standard comprehensive screening , including medical history, physical examination, laboratory tests, and assessment procedures (Shtasel et al, 1992;Gur et al, 1991). These included the patient edition of the SCID (SCID-P; Spitzer et al, 1996), and scales for measuring symptomatology and functioning administered by investigators trained to a criterion reliability of 0.90, intraclass correlation (Shtasel et al, 1992). Entry criteria included (a) a diagnosis of schizophrenia or schizophreniform disorder by DSM-IV criteria, (b) no concomitant axis I or II disorder, including past or present substance abuse or dependence, and (c) no medical or neurological disorder that may affect brain function.…”
Section: Methods Participantsmentioning
confidence: 99%
“…For example, in their original formulation and description of the QLS, Henrichs et al (1984) showed that 52% of the variance in their study was explained by an Interpersonal Relations factor consisting of items 1-8 of the scale, while only 22% of the variance was explained by the other three factors combined. More recently, in a study of sex differences in clinical expression of schizophrenia (Shtasel et al, 1992), we showed that a factor analysis of QLS ratings for 107 patients with schizophrenia revealed three factors: (1) social functioning (items 2-8, 16), (2) engagement (items 1, 13-15, 18-21), and (3) vocational functioning (items 9-11, 12, 17). Others have noted that the four subscales of the QLS are highly related, and provide little additional information beyond the total score.…”
Section: Introductionmentioning
confidence: 98%
“…It is generally accepted that the symptom profile and severity of symptoms are very similar for patients with established schizophrenia and psychosis. 116 These QoL values are therefore potentially useful for the economic evaluation and are reviewed and reported in Appendix 9. As Voruganti and colleagues 117 reported later results from the same study as Awad and colleagues 52 only the study by Voruganti and colleagues 117 is summarised in Appendix 9.…”
Section: Review Of Utility-based Qol Papers In Fepmentioning
confidence: 99%